The Impact of Liquid Organic Fertilizer on Growth and Crop Production of Melon (Cucumis melo L.) - Lisdayani; Candra, Ifan Aulia (Jurnal Online Pertanian Tropik, 2022)
Melon (Cucumis melo L.) is one of the most popular fruit commodities in Indonesia, thanks to its sweet, wonderful flavor, as well as its high nutritional content and nutritional value. Consumer demand for melons is very high, both locally and internationally, although the sugar level of this particular melon is not too sweet. A melon (Cucumis melo L.) is a herbaceous annual plant that grows on vines and is a member of the cucumber family. This study aimed to determine the optimum concentration of cow urine for development (Cucumis melo L.). The experiment used a fully randomized design (CRD) with one factor, namely the concentration of 6-level bio urine, namely B0 = 0 percent bio urine, B1 = 10 percent bio urine, B2 = 20 percent bio urine, B3 = 30 percent bio urine, B4 = 40 percent bio urine, and B5: 50 percent bio urine from 100 ml/plant recommendation. The research findings indicated that application of bio-liquid organic fertilizer (POC) to cow urine may increase: plant length, stem diameter, number of male flowers, and number of female flowers with the best 10 percent POC bio-cow urine. Melon growing can produce 10 percent bio-liquid organic fertilizer (POC) from cow urine.